2007
DOI: 10.1007/s00249-007-0135-5
|View full text |Cite|
|
Sign up to set email alerts
|

Stability and fusion of lipid layers on polyelectrolyte multilayer supports studied by colloidal force spectroscopy

Abstract: The interaction between lipid layers supported by polyelectrolyte multilayer cushions has been studied by means of colloidal force spectroscopy. In a typical experiment, a colloidal probe engineered with a layer-by-layer film and a lipid bilayer on top is approached to a planar surface coated in a symmetrical way. Kinks of a few nanometres in width appear when lipid layers are pressed together--reflecting either fusion processes between lipid layers or membranes, or the penetration of polymer blobs into or thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The flickery bis-gA opening (patch-clamp electrophysiology) indicated the possibility for simultaneous ionic conduction across multiple bilayers in the lipid-coated microspheres, which is a feature that can be exploited in the utilization of the system in a physiologically responsive drug release microcapsule. The existence of multiple bilayers, especially for the case of PClipids, was suggested in the colloidal force spectroscopy studies from Kohler et al [31] Those colloidal force spectroscopy studies also suggested the possibility of incomplete lipid-covering over polyelectrolytes, especially with PC/cholesterol mixed bilayers as we have utilized in the present report. However, our diffusion experiments with lipid-coated microcapsules indicated that the lipid coating provided a good insulating seal.…”
Section: Full Papermentioning
confidence: 54%
See 3 more Smart Citations
“…The flickery bis-gA opening (patch-clamp electrophysiology) indicated the possibility for simultaneous ionic conduction across multiple bilayers in the lipid-coated microspheres, which is a feature that can be exploited in the utilization of the system in a physiologically responsive drug release microcapsule. The existence of multiple bilayers, especially for the case of PClipids, was suggested in the colloidal force spectroscopy studies from Kohler et al [31] Those colloidal force spectroscopy studies also suggested the possibility of incomplete lipid-covering over polyelectrolytes, especially with PC/cholesterol mixed bilayers as we have utilized in the present report. However, our diffusion experiments with lipid-coated microcapsules indicated that the lipid coating provided a good insulating seal.…”
Section: Full Papermentioning
confidence: 54%
“…An additional and intriguing aspect of variations in the kinetics of the gating of incorporated membrane-spanning bis-gA ion channels is the possibility to gain further insight into the mechanisms underlying instability in the lipid coating of polyelectrolyte supports. Measuring the kinetics of channel open/ close activity could be a valuable addition to techniques such as colloidal force spectroscopy [31] in enhancing an understanding of the mechanisms of interaction between lipid bilayers and polyelectrolyte supports. Notwithstanding, the microcapsule system that we report provides a platform for the development of a sealed microcontainer for drug delivery or smart sensing that can navigate in the physiological environment and be controlled with physiologically relevant stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, lipid layers can be formed on polyelectrolyte multilayer coated colloidal particles. [25][26][27] This brings a considerable advantage over the use of flat macroscopic surfaces because powerful particle-based experimental techniques such as flow cytometry (FACS) can be applied.…”
Section: -24mentioning
confidence: 99%